to solve the equation, factor x^2-4x-5 using formula x^2+left(a+b ight)x+ab=left(x+a ight)left(x+b ight). Lớn find a & b, mix up a system to lớn be solved.

Bạn đang xem: Solve the inequality: x

Since ab is negative, a and b have the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. The only such pair is the system solution. 2x2-4x-5=0 Two solutions were found : x =(4-√56)/4=1-1/2√ 14 = -0.871 x =(4+√56)/4=1+1/2√ 14 = 2.871 Step by step solution : Step 1 :Equation at the over of step 1 : (2x2 - 4x) - 5 = 0 ...
(3x2)-4x-5=0 Two solutions were found : x =(4-√76)/6=(2-√ 19 )/3= -0.786 x =(4+√76)/6=(2+√ 19 )/3= 2.120 Step by step solution : Step 1 :Equation at the kết thúc of step 1 : (3x2 - 4x) - 5 = 0 ...
4x2-4x-5=0 Two solutions were found : x =(4-√96)/8=(1-√ 6 )/2= -0.725 x =(4+√96)/8=(1+√ 6 )/2= 1.725 Step by step solution : Step 1 :Equation at the over of step 1 : (22x2 - 4x) - 5 = 0 ...
5x2-4x-5=0 Two solutions were found : x =(4-√116)/10=(2-√ 29 )/5= -0.677 x =(4+√116)/10=(2+√ 29 )/5= 1.477 Step by step solution : Step 1 :Equation at the end of step 1 : (5x2 - 4x) - 5 = ...
6x2-4x-5=0 Two solutions were found : x =(4-√136)/12=1/3-1/6√ 34 = -0.638 x =(4+√136)/12=1/3+1/6√ 34 = 1.305 Step by step solution : Step 1 :Equation at the over of step 1 : ((2•3x2) - 4x) ...
More Items     To solve the equation, factor x^2-4x-5 using formula x^2+left(a+b ight)x+ab=left(x+a ight)left(x+b ight). To find a and b, mix up a system to be solved.
Since ab is negative, a and b have the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. The only such pair is the system solution.
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as x^2+ax+bx-5. Lớn find a và b, phối up a system lớn be solved.
Since ab is negative, a and b have the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. The only such pair is the system solution.
All equations of the khung ax^2+bx+c=0 can be solved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one when ± is addition & one when it is subtraction.
This equation is in standard form: ax^2+bx+c=0. Substitute 1 for a, -4 for b, & -5 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^2+bx=c.
Divide -4, the coefficient of the x term, by 2 lớn get -2. Then showroom the square of -2 lớn both sides of the equation. This step makes the left hand side of the equation a perfect square.
Factor x^2-4x+4. In general, when x^2+bx+c is a perfect square, it can always be factored as left(x+fracb2 ight)^2.

Xem thêm: Bộ Đề Thi Giữa Kì Môn Toán Lớp 9 Môn Toán Mới Nhất, Bộ Đề Ôn Thi Giữa Học Kì 2 Môn Toán Lớp 9

Quadratic equations such as this one can be solved by a new direct factoring method that does not require guess work. To lớn use the direct factoring method, the equation must be in the khung x^2+Bx+C=0.
Let r and s be the factors for the quadratic equation such that x^2+Bx+C=(x−r)(x−s) where sum of factors (r+s)=−B và the product of factors rs = C
Two numbers r và s sum up lớn 4 exactly when the average of the two numbers is frac12*4 = 2. You can also see that the midpoint of r và s corresponds khổng lồ the axis of symmetry of the parabola represented by the quadratic equation y=x^2+Bx+C. The values of r and s are equidistant from the center by an unknown quantity u. Express r & s with respect to variable u.  EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు